Dimensi Metrik Dominasi Pada Graf Globe dan Graf Pendant Globe - Muchammad Abrori; Atifah Rahmah; Deddy Rahmadi (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2026)
The dominating metric dimension of a graph is defined as the minimum cardinality of a set that is both a resolving set and a dominating set. A node is said to be an is a differentiating set if for every two different vertices holds and said to be a set of a dominant if there is at least one node adjacent to the set domination. The Globe graph is a graph obtained from two protected vertices connected by paths of length two. The Pendant Globe Graph is is a graph obtained from a globe graph by adding paths along it . This research discusses the metric dimensions and dominant metric dimension on the globe graph for as well as metric dimensions on the pendant globe graph for and . The method in this research begins with the concept of metric dimension, the concept of metric dimension then dominant continued with the introduction of the characteristics of globe graphs and pendant globe graphs. Furthermore, the metric dimension and dominance dimension will be sought in globe graphs and pendant globe graphs for vertices.